Síntese e caracterização de nanoparticulas de ferrita do tipo Mn0,75Zn0,25 FeyO4 para aplicação biomédica: Marcadores de tumores - Moura, Tiago Fernando Alves de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The application of magnetic nanoparticles in medicine has been highlighted, as these can serve as markers in the diagnosis of cancer in techniques as alternating current biosusceptometry (ACB) and nuclear magnetic resonance (NMR), which do not use ionizing radiation. The present work aims to optimize the physical properties of the manganese and zinc ferrites, with the unit formula Mn0.75Zn0.25FeyO4, by varying the nominal composition of iron (y), namely with values of "y" equal to 1 , 5; 1.7; 2.0; 2.4 and 2.8, and the concentration of the precipitating agent. The co-precipitation method was used for the synthesis and the obtained samples were characterized by the following techniques: (i) Dispersive Energy X-ray Analysis (EDX), which provided the chemical composition and the efficiency of preparation method to achieve proposed materials; (ii) X-ray diffraction (XRD) for the determination of the crystalline structure and the presence or absence of the secondary phase, where the refinement by Rietveld Method provided structural data regarding the lattice parameters and crystallite size, and (iii) Alternating Current Biosusceptometry (ACB), which provided the magnetic response of the synthesized samples. The co-precipitation method provides Mn0.75 Zn0.25FeyO4 single-phase material under a cubic structure (spinel, ICSD 28515), with the composition close to the nominal one. The results of the ACB showed that the susceptibility is higher when the amount of iron is in excess than the stoichiometric value (of y = 2,0). The correlation with XRD results showed that there is influence of the occupation of spinel sites on the magnetic behavior. It has also been shown that there is (not very clear) influence of crystallinity (size of crystallites) on magnetic behavior

A aplicação de nanopartículas magnéticas na medicina tem se destacado, pois estas podem servir de marcadores no diagnóstico de câncer em técnicas como biossusceptometria de corrente alternada (BAC) e ressonância magnética nuclear (RMN), que não usam radiação ionizante. O presente trabalho tem como proposta otimizar as propriedades físicas das ferritas de manganês e zinco, de fórmula unitária Mn0,75Zn0,25FeyO4, variando-se a composição nominal de ferro (y), a saber, com valores de "y" iguais a 1,5; 1,7; 2,0; 2,4 e 2,8, e a concentração do agente precipitante. Utilizou-se do método de coprecipitação para a síntese e as amostras obtidas foram caracterizados mediante as seguintes técnicas: (i) Energia Dispersiva de Raios X (EDX), que proporcionou a composição química e eficiência do método na preparação dos materiais obtidos; (ii) Difração de Raios X (DRX), para a determinação da estrutura cristalina das ferritas e a presença ou não da fase secundária, sendo que o refinamento dos dados com o Método de Rietveld forneceu dados estruturais a respeito dos cristais como parâmetros de rede e tamanho de cristalitos e (iii) a Biossusceptometria de Corrente Alternada (BAC), que proporcionou a resposta magnética das amostras sintetizadas. O método de copreciptação permite obter materiais monofásicos de ferrita Mn0,75Zn0,25FeyO4 com estrutura cúbica de face centrada (espinélio, ICSD 28515) com composição próxima a nominal. Os resultados da BAC mostraram que a susceptibilidade é maior quando a quantidade de ferro está em excesso em relação ao valor estequiométrico (de y=2,0). A correlação com os resultados de DRX mostrou que existe influência da ocupação de sítios do espinélio no comportamento magnético. Mostrou-se ainda que existe uma relação, embora não clara, entre a cristalinidade (tamanho de cristalitos) e o comportamento magnético
Keywords: Synthesis; Manganese and zinc ferrites; Coprecipitation method; Characterization; Alternating current biosusceptometry; Magnetic materials; Síntese; Ferritas de manganês e zinco; Método de coprecipitação; Caracterização; Biossusceptometria de corrente alternada; Materiais magnéticos